The Effect of School Principal Leadership and School Climate on Teacher Performance - AR, Novi Rozalita; Sabandi, Ahmad (Graduate Program Magister Manajemen Pendidikan, 2022)
This study aims to see how much far the independent variable affects the dependent variable. This study explains and sees how much influence the principal's leadership, school climate has on teacher performance at SMPN Sangir District, South Solok Regency. The type of research used is correlational quantitative research. The population is 81 teachers of SMP Negeri in Sangir sub-district, from the population obtained a sample of 44 teachers, the sample was taken using stratified proportional random sampling technique. The instrument used to collect data for the three research variables was a Likert with five alternative answers, namely: always, often, sometimes, rarely, and never. The findings of this study indicate that the principal's leadership has a direct effect on teacher performance by 19.2%. school climate has an effect on teacher performance by 19.8%. Principal leadership and school climate together affect teacher performance by 32.6%. The research findings can be used in order to improve teacher performance through principal leadership and school climate at SMP N Sangir District, South Solok Regency. Through the findings of this study, we can conclude that teacher performance can be improved by improving principal leadership and school climate.Â